Empirical evaluation of weak-form efficient market hypothesis in Ugandan securities exchange - Kalu O. Emenike; Kirabo K. B. Joseph (Journal of Contemporary Economic and Business Issues, 2018)
An efficient stock market plays an important role in stimulating economic development through providing a channel for mobilising domestic savings and facilitating the allocation of financial resources from dormant to more productive activities. This paper evaluates the Ugandan Securities Exchange (USE) for evidence of a weakform efficient market hypothesis in the context of random walk model, using both linear and non-linear models. The preliminary analysis from the USE daily returns, for the September 1, 2011 to December 31, 2016 period, shows negative skewness, leptokurtosis, and non-normal distribution. Estimates from the linear models show evidence of weak-form efficiency. Conversely, estimates from non-linear models show evidence against weak-form efficiency of the USE. The study concludes that USE returns may only be predicted using non-linear models and fundamental analysis. In other words, linear models and technical analyses may be clueless for predicting future returns.
Keywords: G14; 330; Weak-form efficiency; random walk; linear and non-linear models; Ugandan securities exchange